Comparison of static postural stability between individuals with ankle sprain injuries and ACL reconstruction individuals - Mohseni Farnaz; Memar Raghad; Sadeghi Heydar (Türk Spor ve Egzersiz Dergisi)
This study aimed to determine static postural stability between individuals with ankle sprain injuries and ACL reconstruction. Thirty subjects (74.10±8.82 kg, 180.05±7.64 cm 19.94±2.18 yr) were divided into three groups which include ACL-R (n=10), ankle sprain (n=10) and healthy individuals (n=10). Subjects were required to balance on a single leg and remain motionless for 30s on an emed platform. The results were compared by center of pressure sway (cop), average velocity of COP and excursion of COP as measured by a pressure platform (emed-C50, novel, Germany). The ankle sprain and ACL-R groups had greater sway area than the healthy group. In addition there were significant differences between ankle sprain, ACL-R and healthy groups in COP excursion and the average velocity of COP in all the great measures are belonged to ACL-R specially ankle sprain. This study suggested that individuals with ACL-R and ankle sprain had changes in posture stability.